Psychological distress among healthcare professionals at the frontlines: anaesthesiologists’ perspective - Tsan, Samuel Ern Hung; Anand, Kamalanathan; Wang, Chew Yin (Routledge, 2021)
The COVID-19 pandemic raging in Malaysia has been one of the greatest challenges so far since its formation, and standing at the forefront of this “war” are Malaysian healthcare practitioners. We sought to capture a snapshot of the psychological distress encountered by those in the medical profession standing at the frontlines of the fight against COVID-19, by carrying out a cross-sectional study to investigate the prevalence of burnout and depression risk among anaesthesiology clinicians in a nationally designated exclusive COVID-19 hospital. We utilised validated questionnaires and included all the clinicians (n=88) in the Anaesthesiology and Intensive Care Department. This study was conducted throughout the month of May 2020, which corresponded to the end of the first Malaysian Government Movement Control Order (from 18th March to 3rd May 2020). Results showed that more than half of anaesthesiologists managing COVID-19 patients suffered from burnout, and up to 67% had a high risk of depression. Both burnout and depression are significantly associated with one another. The findings are discussed, followed by recommendations for preventative strategies to increase the mental fortitude of healthcare practitioners in Malaysia.